Retinal ganglion cell layer correlates with cognitive involvement in Alzheimer's disease and mild cognitive impairment. Issue 3 (March 2016) - Huang, S.; Ferrari, L.; Coppi, E.; Vitali, F.; Magnani, G.; Comi, G.; Leocani, L.
Abstract : Introduction: Optical coherence tomography (OCT) allows non-invasive measurement of retinal nerve fiber layer (RNFL) which is a potential marker of neuronal loss for monitoring the natural course and treatment effect of Alzheimer's disease (AD). According to previous studies, the ganglion cell layer (GCL) might be more sensitive than RNFL in detecting early neuronal degeneration. Here we aim to demonstrate the potential of GCL as an alternative for evaluating neuronal loss in patients with AD. Materials and methods: Eighteen patients (seven with AD and eleven with MCI) were included and peripapillary scans of both eyes were acquired with spectral domain OCT. Correlations between GCL, RNFL, and minimental state examination (MMSE) was performed using Pearson's correlation. Results: The severity of cognitive decline (raw MMSE) was positively associated with thinning of GCL in both left ( r  = 0.665, p  = 0.003) and right eye ( r  = 0.569, p  = 0.014), while no correlation was found between RNFL and MMSE score. Conclusion: Our result suggested that the GCL may offer more functional relevant information than the RNFL, which makes it a potential biomarker for monitor AD progression.